2006
DOI: 10.1007/bf03347368
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial to evaluate the efficacy of ultrasound-guided laser photocoagulation for treatment of benign thyroid nodules

Abstract: This randomized controlled study was designed to test the efficacy and safety of percutaneous ultrasound (US)-guided laser photocoagulation (PLP) for treatment of subjects with compressive symptoms due to benign thyroid nodules and/or at high surgical risk. Twenty six subjects were randomized to the intervention (no. 13, age 68+/-3 yr, mean+/-SEM) or observation (no. 13, age 71+/-2 yr) groups. In the control group, the volume of nodules did not significantly change over the 30 week period of observation. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 9 publications
0
41
2
Order By: Relevance
“…Although the energy deposited per milliliter nodule tissue has varied in the available studies, a statistically significant correlation between energy deposited and nodule volume reduction could not be demonstrated (18,21,22), and only few studies have been able to demonstrate such a correlation (34,35). This suggests that in the individual patient, it is not easy to determine the optimal energy level.…”
Section: Discussionmentioning
confidence: 99%
“…Although the energy deposited per milliliter nodule tissue has varied in the available studies, a statistically significant correlation between energy deposited and nodule volume reduction could not be demonstrated (18,21,22), and only few studies have been able to demonstrate such a correlation (34,35). This suggests that in the individual patient, it is not easy to determine the optimal energy level.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of permanent hypothyroidism was low (only three patients) [63,65]. Valcavi et al have found that thyroid pericapsular bleeding developed in almost 2 % of patients, but this disappeared in 3-4 weeks.…”
Section: Complicationsmentioning
confidence: 94%
“…The patient is placed in a supine position with neck hyperextended. The procedure is performed under ultrasound system guidance [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74]. In most studies, a 21-G needle is inserted into the lesion along its longest axis.…”
Section: La Devices and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with such tumors are not suitable for surgery, radiotherapy, and chemotherapy. With these three treatments precluded, the possible and available treatments must be local and non-invasive, with image precise monitoring, and real-time confirmation, and these options include laser [1] , cr yotherapy [2] , photodynamicmic therapy [3,4] , radioactive particle [5] and high intensity focused ultrasound (HIFU) [6] . HIFU is a new treatment for solid malignant tumors, which emerged in recent years [7,8] .…”
Section: Introductionmentioning
confidence: 99%